2014
DOI: 10.1007/s11356-014-3863-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some selected herbs on arsenic-affected cattle in Nadia District, West Bengal, India

Abstract: Arsenic poisoning due to contaminated subsoil water is one of the most alarming environment hazards in West Bengal, India. Cattle are also affected by arsenic due to ingestion of arsenic contaminated water, paddy straw, crops and vegetables. Thirty milch cattle having arsenic content in the range of 3.5 to 4.5 mg/kg in hair were chosen for this experiment from cattle of five respective villages in Nadia District, West Bengal, India. The cattle were divided into three groups containing 10 animals each. Group I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…It alters all the haematological and biochemical changes caused by chronic arsenic poisoning. It also gives protection from the DNA damage caused by arsenic [25].…”
Section: Dietary Supplements For Arsenic Poisoningmentioning
confidence: 99%
See 1 more Smart Citation
“…It alters all the haematological and biochemical changes caused by chronic arsenic poisoning. It also gives protection from the DNA damage caused by arsenic [25].…”
Section: Dietary Supplements For Arsenic Poisoningmentioning
confidence: 99%
“…It has hepatoprotective, antimicrobial, anti-inflammatory and antihyperglycemic effect. E. alba powder helps to eliminate arsenic from the body; it brings the arsenic induced hematological and biochemical alterations to normal level; it has cytoprotective and DNA protective activities in chronic arsenicosis affected cattle [25].…”
Section: Dietary Supplements For Arsenic Poisoningmentioning
confidence: 99%
“…A large number of researches confirmed the beneficial effect of Glycine max [122], Sesamum indicum [123], Satureja hortensis [124] Withania somnifera [125,126], Ipomea aquatica [127], Tamarindus indica [128], Royal jelly [129], and Terminalia chebula [130] on arsenic and cadmium toxicities reduction. Concerning the effects of natural products on arsenic toxicity in ruminants, it was reported that Curcuma longa, Zingiber officinale, and Amaranthus spinosus have eliminated the absorption of arsenic from the bovine body and protected against DNA fragmentation in these species [131,132]. In a recent study, Curcuma longa powder and Paederia foetida powder were effectively able to remove arsenic from the body of arsenicosis induced by sodium arsenite in sheep.…”
Section: Arsenic and Cadmium Toxicity Preventionmentioning
confidence: 99%
“…It also inhibits arsenic induced cell damage by blocking the c-Jun amino-terminal kinase (JNK) pathway. Hazarika et al (2015) reported that treatment with turmeric powder alone or turmeric and Amaranthus spinosus or turmeric and Eclipta alba resulted in reduced arsenic deposition in body of cattle by increasing the excretion, even its encapsulated form was found to be more effective (Sankar et al, 2015). Ginger contains many flavonoids and phenol compounds.…”
Section: Herbal Drugmentioning
confidence: 99%
“…Arsenic may produce ROS which may damage DNA or arsenic may directly damage the sulfhydryl group of DNA which stands as a factor of carcinogenicity (Zhang et al, 2015). Oxidative damage which is a pronounced effect of arsenic toxicity can be treated by various nutritional anti-oxidants treatments such as vitamin E (Mohanta et al, 2014), vitamin C (Singh et al, 2010); herbal treatments like turmeric (Hazarika et al, 2015), ginger root (Biswas et al, 2016); minerals such as zinc (Ganger et al, 2016) and selenium. Saccharomyces cerevisiae have property of binding with arsenic in acidic medium in water which can protect it from being absorbed in body.…”
Section: Introductionmentioning
confidence: 99%